2011
DOI: 10.1007/s10661-011-2239-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sediment quality in the Mediterranean Sea–Boughrara lagoon exchange areas (southeastern Tunisia): GIS approach-based chemometric methods

Abstract: Concentrations of selected heavy metals (Cd, Pb, Zn, Cu, Mn, and Fe) in surface sediments from 66 sites in both northern and eastern Mediterranean Sea-Boughrara lagoon exchange areas (southeastern Tunisia) were studied in order to understand current metal contamination due to the urbanization and economic development of nearby several coastal regions of the Gulf of Gabès. Multiple approaches were applied for the sediment quality assessment. These approaches were based on GIS coupled with chemometric methods (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In the southern localities in the Gulf of Gabès (SF, GA, ZA, and BG), Cd concentrations were the highest among the studied sites. In this area, the major factor behind this metallic pollution is phosphogypsum wastes as showed in several previous works (e.g., Darmoul 1988Darmoul , 1980Darmoul and Vitiello 1980;Kharroubi et al 2012;Ayadi et al 2015;El Zrelli et al 2015). Indeed, high amounts of phosphogypsum are discharged by the phosphate industry in the Gulf of Gabès, being quantified as 11,250 t per day and stretching over big surfaces in the open sea with deleterious effects on biota (Darmoul and Vitiello 1980;Darmoul 1988;Béjaoui et al 2004;Rabaoui et al 2015).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In the southern localities in the Gulf of Gabès (SF, GA, ZA, and BG), Cd concentrations were the highest among the studied sites. In this area, the major factor behind this metallic pollution is phosphogypsum wastes as showed in several previous works (e.g., Darmoul 1988Darmoul , 1980Darmoul and Vitiello 1980;Kharroubi et al 2012;Ayadi et al 2015;El Zrelli et al 2015). Indeed, high amounts of phosphogypsum are discharged by the phosphate industry in the Gulf of Gabès, being quantified as 11,250 t per day and stretching over big surfaces in the open sea with deleterious effects on biota (Darmoul and Vitiello 1980;Darmoul 1988;Béjaoui et al 2004;Rabaoui et al 2015).…”
Section: Discussionmentioning
confidence: 83%
“…In GA, this increase can be explained by the continuous rejection of phosphate industrial wastes directly into the marine environment around the city of Gabès, although many interruptions in the production of the factory occurred during the strikes in 2011. However, in the ZA and BG stations, Cd contamination is probably related to the local hydrodynamics that play a key role in the transport of phosphogypsum from the Gabès chemical pole to the southern locations, reaching the Boughrara lagoon (Kharroubi et al 2012). Taking into account the Cd concentrations recorded in the present study (0.1-19.2 μg/g in whole body and 0.2-31.3 μg/g dw in the coiled portion), as compared to previous investigations with this species in Tunisia, the concentration range in the Gulf of Gabès is similar to that reported by Chouba et al (2008) for the period 2003-2004 (20-25 μg/g dw in the foot and 20-40 μg/g dw in the viscera) and lower than those reported by Gharbi-Bouraoui et al (2008) in the Bizerte lagoon (10.6-18.5 μg/g dw in the viscera).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the southern region of the Gulf of Gabes, Cd concentrations were highest among the studied sites. In this area, the major factor behind this metallic pollution by heavy metals is phosphogypsum wastes, as shown in several previous works [61,[64][65][66][67]. Indeed, high amounts of phosphogypsum are discharged by the phosphate industry in the Gulf of Gabes, quantified at 11,250 tons per day and stretching along large surfaces in the open sea with deleterious effects on biota [60,[64][65]68].…”
Section: Origin Of Trace Element Loading In Surface Waters In Three Gmentioning
confidence: 98%
“…These discharges contain various metals, including Cd (39.8 mg kg ), and others like Hg, Mo, Co, and F [69]. According to Kharroubi et al (2012) [66], the amounts of metals found in the flux of the principal effluents from the industrial pole of Gabes are estimated at 300 kg day 1 for Cd, 200 for Cu, 3,500 for Zn, 50 for Pb, 250 for Mn, and 9,330 for Fe.…”
Section: Origin Of Trace Element Loading In Surface Waters In Three Gmentioning
confidence: 99%